Development of novel molecular tools for the identification of essential genes of Clostridium difficile and a Clostridium tetracycline inducible promoter system - Walker, David J.F. (2012)
Clostridium difficile is the leading cause of nosocomial diarrhoea in the world, and a considerable burden to healthcare services. For colonisation of C. difficile to occur in the gut of an individual, the resident gut flora must first be quantitatively or qualitatively altered, normally through antibiotic treatment for an unrelated infection. At present, broad-spectrum antibiotics such as vancomycin and metronidazole, the frontline choices for the treatment of C. difficile infection; disturb the normal gut flora, suffer from poor recurrence rates, and have received reports of sporadic emergence of resistance. Development of novel narrow-spectrum antimicrobials would circumvent these problems but depend on the identification of novel essential genes. Molecular techniques available to identify and study essential genes in other organisms have not yet been applied to C. difficile. In this study, we identified 208 candidate essential genes via in silico analysis based upon similarity to known Bacillus subtilis essential genes. In order to provide experimental evidence of essentiality, we developed a novel method utilizing partial diploids and functionally characterised three C. difficile genes as essential; CD0274, metK, and trpS. This method not only identified CD0274, a candidate narrow-spectrum drug target and the first essential genes in C. difficile, but also provides a reliable method to identify further essential genes for novel antimicrobial targeting. In addition, we developed a lac repressor system, a rationally designed theophylline-responsive riboswitch, and most importantly, a Tet inducible promoter system able to conditionally control expression of a catP reporter through a wide dynamic range in both C. difficile and C. sporogenes, to maximum induction factors of 192.89 and 1,275.63, respectively. The combinations of these characteristics make this Tet system not only a powerful tool for identifying essential genes, but bestows a great potential for further analysing gene function far beyond the scope of this project.